Estimating the role of climate changes on international tourist flows: evidence from Mediterranean Island States - Katircioglu, Setareh; Cizreliogullari, Mehmet Necati; Katircioglu, Salih (Springer Heidelberg, 2019)
This article examines the role of climate change on tourist flows to Malta, Cyprus (north), and Cyprus (south) which are major tourist destinations in the Mediterranean. Results from time series analyses reveal that climate change positively impacts on foreign tourist flows to these island states. Thus, this finding is reasonable where we argue that global warming leads to increases in international tourist arrivals to small island states. This paper has also found statistically significant effects of overall energy consumption on foreign tourist arrivals to Malta and Cyprus revealing that energy efficiency policies are essential in small island states.
Keywords: Climate change; Carbon emissions; Tourism; Islands